Vegetative Growth Response of Chili Pepper Plants (Capsicum frutescens L.) Absolut 69 Variety to Rice Husk Biochar Application - Zahro, Nurfadila; Fadhilah, Ines; Nadita Cahya, Dhea; Suciaty, Tety (Jurnal Agrosci, 2024)
Chili pepper (Capsicum frutescens L.) is one of the raw material crops with high economic value in Indonesia. This research aims to determine the effect of rice husk biochar on the vegetative growth of cayenne pepper plants (Capsicum frutescens L.) Absolute 69 variety. This research was conducted from June to August 2024 in Kertasura Village, Kapetakan District, Cirebon Regency. The technique used in this research was a randomized block design (RAK) with six treatments. The rice husk biochar treatments tested consisted of B0 (0 t/ha control), B1 (2.5 t/ha), B2 (5 t/ha), B3 (7.5 t/ha), and B4 (10 t /ha) and B5 (12.5 t/ha) and each treatment was repeated four times so that resulting in 24 trials. The parameters observed were plant height, number of leaves, stem diameter, root length, root volume, and plant dry weight. The results showed that applying rice husk biochar affected all parameters except root volume. Providing 10 tons of rice husk biochar per hectare is most effective for the vegetative growth of chili peppers.